Dietary Iron Deficiency Modulates Adipocyte Iron Homeostasis, Adaptive Thermogenesis, and Obesity in C57BL/6 Mice. Issue 10 (12th August 2021) - Yook, Jin-Seon; Thomas, Shalom Sara; Toney, Ashley Mulcahy; You, Mikyoung; Kim, Young-Cheul; Liu, Zhenhua; Lee, Jaekwon; Chung, Soonkyu
ABSTRACT: Background: Adaptive thermogenesis is an iron-demanding pathway, significantly contributing to whole-body energy expenditure. However, the effects of iron-deficient diets on adaptive thermogenesis and obesity remain unknown. Objectives: We aimed to determine the impact of dietary iron deficiency on iron homeostasis in adipocytes, adaptive thermogenic capacity, and metabolic consequences in obesity. Methods: C57BL/6 male mice were assigned to either the iron-adequate (IA, 35 ppm) or the iron-deficient group (ID, 3 ppm) at weaning. Upon 8 wk of age, both IA and ID groups received an isocaloric high-fat diet (45% kcal from fat) for 10 wk, maintaining the same iron content. Mice ( n = 8) were used to determine the iron status at the systemic and tissue levels and lipid metabolism and inflammatory signaling in adipose tissue. The same mice were used to evaluate cold tolerance (4°C) for 3 h. For assessing adaptive thermogenesis, mice ( n = 5) received an intraperitoneal injection of β3-adrenoceptor agonist CL316243 (CL) for 5 d. Results: Compared with the IA group, the ID group had nonanemic iron deficiency, lower serum ferritin (42.8%, P < 0.01), and greater weight gain (8.67%, P < 0.05) and insulin resistance (159%, P < 0.01), partly due to reduced AMP-activated protein kinase activation (61.0%, P < 0.05). Upon cold exposure, the ID group maintained a core body temperature 2°C lower than the IA group. The ID group had lower iron content (47.0%, P < 0.01) in the inguinal adipose tissue (iWAT) than the IA group, which was associated with impaired adaptive thermogenesis. In response to CL, ID mice showed decreased heat production ( P < 0.01) and defective upregulation of beige adipocyte-specific markers, including uncoupling protein 1 (41.1%, P < 0.001), transferrin receptor 1 (47.5%, P < 0.001), and mitochondrial respiratory chain complexes ( P < 0.05) compared with IA mice. Conclusions: Dietary iron deficiency deregulates iron balance in the iWAT and impairs adaptive thermogenesis, thereby escalating the diet-induced weight gain in C57BL/6 mice.